UNCOVERING HIDDEN MESSAGES: AN ANALYSIS OF METAPHORS IN JKT48'S "MAHAGITA" ALBUM - Zahra, Intan Karima; Wibowo, Hanafi (KLAUSA (Kajian Linguistik, Pembelajaran Bahasa, dan Sastra), 2024)
This research examines the metaphorical language in JKT48's Mahagita album to explore how figurative expressions convey deeper emotions and themes within the lyrics. By applying Lakoff and Johnson's Conceptual Metaphor Theory, the study classifies metaphors from selected songs into three types: structural, ontological, and orientational, each contributing to themes such as love, hope, struggle, and personal development. This qualitative descriptive analysis focuses on the lyrics of eleven songs to uncover how these metaphors enhance listeners' emotional engagement and comprehension. Findings indicate that ontological metaphors represent the largest segment, accounting for 47.5%, illustrating abstract feelings through tangible comparisons, such as “Hidup bagaikan pesawat kertas” (Life is like a paper airplane), which highlights the unpredictability and fragility of life. Through metaphor, the lyrics of JKT48 establish a profound emotional connection that resonates with listeners, demonstrating the effective application of figurative language in music to convey intricate emotions and concepts.